Opportunities and challenges with the protection of ancient mining sites in mountain landscapes: A case study of the Kopaonik - Marić M. (Journal of Mining and Metallurgy. Section A: Mining)
The remains of ancient mining activities represent a significant part of Serbia's archaeological sites in the mountain landscapes, which are not yet officially treated as cultural heritage. This type of assets poses a significant challenge for cultural heritage protection services, as it requires cooperation between experts for the protection of natural and cultural values and other stakeholders, which is not yet established. In addition, the concept of mining landscapes is not recognized in current legislation, which further complicates the legal protection of the remains of ancient mines, which are recognized by scholars as an essential segment in the interpretation of historical processes of significance, such as Roman imperialism in the Balkans. Against this background, the paper presents the decades of archaeological research at Kopaonik, which has led, among other aspects, to an attempt to establish a uniform practice of treating ancient mines, together with settlements and associated infrastructure, as an integral part of the mountain landscape, despite the absence of any legal regulation. The study examines the challenges associated with the formal-legal preservation of sites with historic mining, taking into account the possibility of permanent destruction. Finally, an outlook is given on the future of the protection of (pre)historic mines in Serbia as an important element of the country's geocultural resources.